2018
DOI: 10.1002/chem.201704207
|View full text |Cite
|
Sign up to set email alerts
|

Safe‐by‐Design Ligand‐Coated ZnO Nanocrystals Engineered by an Organometallic Approach: Unique Physicochemical Properties and Low Toxicity toward Lung Cells

Abstract: The unique physicochemical properties and biocompatibility of zinc oxide nanocrystals (ZnO NCs) are strongly dependent on the nanocrystal/ligand interface, which is largely determined by synthetic procedures. Stable ZnO NCs coated with a densely packed shell of 2-(2-methoxyethoxy)acetate ligands, which act as miniPEG prototypes, with average core size and hydrodynamic diameter of 4-5 and about 12 nm, respectively, were prepared by an organometallic self-supporting approach, fully characterized, and used as a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 32 publications
(59 citation statements)
references
References 91 publications
(48 reference statements)
3
47
1
Order By: Relevance
“…Moreover, we have also emphasized the essential role of the coordination state of the oxygenated organoaluminum and organozinc compounds, as well as the geometric requirements of an O 2 molecule approaching the metal centre . Apart from the fundamental aspects, these systematic studies have advanced rational design of metal alkyl/air systems as radical initiators for organic reactions, stoichiometric and catalytic asymmetric epoxidation of enones and pave the way to well‐defined metal alkoxides (not accessible through the classical alcoholysis path) as potential initiators of cyclic esters polymerization as well as to a new approach for the preparation of semiconductor zinc oxide quantum dots based on organozinc/air systems …”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, we have also emphasized the essential role of the coordination state of the oxygenated organoaluminum and organozinc compounds, as well as the geometric requirements of an O 2 molecule approaching the metal centre . Apart from the fundamental aspects, these systematic studies have advanced rational design of metal alkyl/air systems as radical initiators for organic reactions, stoichiometric and catalytic asymmetric epoxidation of enones and pave the way to well‐defined metal alkoxides (not accessible through the classical alcoholysis path) as potential initiators of cyclic esters polymerization as well as to a new approach for the preparation of semiconductor zinc oxide quantum dots based on organozinc/air systems …”
Section: Introductionmentioning
confidence: 96%
“…[33,34] Apart from the fundamental aspects, these systematic studies have advanced rational designo fm etal alkyl/airs ystemsa sr adicali nitiators for organic reactions, [35][36][37] stoichiometric [38,39] and catalytic asymmetric epoxidation of enones [11,14,40] and pave the way to welldefined metal alkoxides (not accessible through the classical alcoholysis path) as potentiali nitiators of cyclic esters polymerization [25,41] as well as to an ew approach for the preparation of semiconductor zinc oxide quantum dots based on organozinc/ air systems. [42][43][44][45][46] Notably,t he oxygenationc hemistry of magnesium alkyls has remained anu ndeveloped area of research due to difficulties to control the respective reactions ystemsr esulting from the exceptionali nstability of MgOOR species. As early as the beginningo ft he XX th centuryB odroux [47] and Bouveault [48] independently observed that oxygenationo fR MgX compounds afforded the corresponding ROH alcohols after the standard workup procedure.…”
Section: Introductionmentioning
confidence: 99%
“…8 Simultaneously, we also demonstrated that ZnO NCs obtained by this organometallic procedure exhibit essentially a very low negative impact on mammalian cell lines. 9 We anticipated that the observed low cytotoxicity stems from the NC effective surface passivation and the impermeable organic shell. Thus, we wondered if this type of well-passivated ZnO NC could be prone to the ligand shell functionalization using CuACC while retaining the PL properties of the nanoparticles.…”
mentioning
confidence: 99%
“…The anticipated impermeability perfectly correlates with the above-mentioned very low negative impact of the analogously synthesized ZnO NCs on mammalian cell lines. 9 Scheme 1 Preparation of ZnO NCs: (i) the precursor synthesis, (ii) its transformation to una-ZnO NCs, and (iii) the functionalization of brightly luminescent una-ZnO NCs by the CuACC reaction affording tr-NCs with preserved PL. To highlight the superiority of our synthetic method over most common inorganic sol-gel processes, 13 we performed the analogous functionalization mediated by CuACC for una-coated ZnO NCs obtained by the traditional inorganic method (hereafter denoted as inorgA-ZnO).…”
mentioning
confidence: 99%
“…More recently, we have elaborated the one‐pot self‐supporting organometallic (OSSOM) procedure based on the controlled exposition of a [EtZn(X)]‐type precursor (X=monoanionic organic ligand) to air leading to ZnO NCs coated with an organic shell composed of surface‐anchored X‐type ligands . The OSSOM process is thermodynamically controlled and affords stable, bio‐safe and well‐passivated ZnO NCs with ultra‐long‐lived luminescence …”
Section: Figurementioning
confidence: 99%